2005
DOI: 10.1111/j.1600-051x.2005.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal infections and pre‐term low birth weight: a case‐control study

Abstract: The present findings indicated that when subgingival bacteria were evaluated together, P. micros and C. rectus may have a role in increasing the risk for PLBW, although no single bacteria exhibited any relation with the risk of PLBW. Further studies are required to better clarify the possible relationship between periodontal diseases and PLBW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
125
3
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(163 citation statements)
references
References 38 publications
18
125
3
17
Order By: Relevance
“…Subgingival plaque samples were collected as described previously [28] from the two deepest pockets of the dentition. Prior to sampling, the sample teeth were isolated with cotton rolls and the sites were cleaned of saliva and supragingival plaque using sterile cotton pellets.…”
Section: Subgingival Plaque Samplingmentioning
confidence: 99%
“…Subgingival plaque samples were collected as described previously [28] from the two deepest pockets of the dentition. Prior to sampling, the sample teeth were isolated with cotton rolls and the sites were cleaned of saliva and supragingival plaque using sterile cotton pellets.…”
Section: Subgingival Plaque Samplingmentioning
confidence: 99%
“…Preeclampsia also involves increase in inflammatory cytokines in the blood stream, which makes adjusting for preeclampsia in our study important before any conclusion can be made. On the other hand, many studies did not find a positive correlation between periodontal disease and preterm labor [28][29][30][31][32]. Based on these results they do not support a specific drive to improve periodontal health of pregnant women as a means of improving pregnancy outcomes [28].…”
Section: Discussionmentioning
confidence: 80%
“…A study conducted by Buduneli N. et al (2005) showed results of high levels of P. micros and C. rectus in mothers delivering LBW infants [19]. A study from a cohort of young minority women in New York, have found that PLBW mothers had significantly higher levels of T. forsythensis and C. rectus, although clinical periodontal status revealed no significant differences between the two groups [13].…”
Section: Discussionmentioning
confidence: 99%